POLA KOMUNIKASI SINGLE PARENT DALAM MENDIDIK ANAK (Studi Kasus di Desa Banglas Barat, Kecamatan Tebing Tinggi, Kabupaten Kepulauan Meranti) - Arlin Setrina Putri; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
A phenomenon single parent that produces new insights into a structure family.The widespread phenomenon of a single parent, the more the description of the definition of single parent itself. Single parent is a person who did duty as a parent (father or mother) alone, having lost or separated partner. The phenomenon that occurs in the field is a single parent working with a small income to meet daily needs and there are successful and unsuccessful in educating their children, as well as the difficulty of dividing their time between work and children.This study used a qualitative descriptive study. Informants consisted of five people who is the committee's mother Single Parent from Desa Banglas Barat, Kecamatan Tebing Tinggi, Kabupaten Kepulauan Meranti using purposive technique sampling.The aim of this study was to determine the pattern of single parent communications made in educating children and to determine the impact of the communication patterns of single parent for a child's development.Data collected by observation, interview and documentation. To achieve the validity of the data in this study, researchers used an extension of participation.The results showed that single parent applying some communication patterns in educating children is authotarian communication patterns, communication patterns permissive, and authoritative communication patterns.Authoritarian is a pattern of communication that the communication links parents are authoritarian, permissive is a pattern of communication that the communication links parents are not concerned with what happened to her son, while authoritative is the communication patterns that observe and appreciate the freedom of children with guidance attentive. Secondly, there is a positive impact and a negative impact on the communication pattern single parent for a child's development.The positive impacts include children avoid contradictory communication from parents and children to be independent and strong personality. While the negative impacts include changes in the behavior of children and child psychology becomes impaired.Keywords : Communication Patterns, Single Parent, educational child.